Tensile buckling of repetitive rods systems with overlapping. (15th August 2020) - Simão, Pedro Dias; da Silva, Vítor Dias
Abstract: In structural engineering, buckling is usually associated with compressive stress and/or shortening deformation states. Recently, several works came to light alerting to the propensity of some structural systems to buckle under tension. Within this context, the present work examines the buckling and post-buckling behaviours of repetitive rods systems under tensile axial loading, and comprises three distinct parts. At first, the tensile stability behaviour of a single rigid rod with an edge section supported by a slider that is forced to follow a pre-established path, developed in the literature that lays behind us, is revisited and related to the buckling behaviour of an alternative two rods system whose buckling propensity arises from a secondary compressed bar overlapping the tensioned one. In the second part of the paper, overlapping is used to create innovative repetitive frames that buckle under tension, in the present case a sequence of lined up rigid rods connected by rotational joints. The tensile critical load shows little change as new modules are added to the system, in clear contrast with the compressive case. The tensile post-buckling behaviour is also assessed, in some cases showing original shapes, and overlapping is used to create repetitive frames with negative thermal expansion coefficient as well. In the third part of the paper, the effects of applying global gradients to the relevant mechanical properties, in the form of smooth variations of the joints rigidities and rods lengths as the module is repeated, on the stability behaviour under tension are assessed. Although these variations are smooth and kept within small values, they provoke significant changes on the tensile buckling load, on the buckling type and on the type of buckling as well. The findings pave the way to the development of innovative repetitive frames, cellular materials, polymer chains and origami structures showing original constitutive behaviours under tension.